PELATIHAN DIGITAL MARKETING UNTUK UMKM SNACK SALSABILA - Rakhmadian, Miftah; Sefaverdiana, Putri Vina; Prasetyo, Novi Eko; Jasmine, Reihanna; Tri Wahyuni, Rima Sampur (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
Digital marketing is the most important part of a company's marketing strategy, where currently information technology and the internet have changed the way of interacting with customers, with digital marketing companies can more easily attract consumers by marketing digitally using social media, besides that digital marketing also makes it easier companies in interacting with consumers. In the current digital era, some MSMEs still carry out their activities in shops or face to face with consumers. These MSMEs are not familiar with digital marketing so consumers are only their regular customers. This community service aims to expand the sales reach and sales turnover of MSMEs in Dusun. Bengkaras, Madiredo Village, Pujon District, Malang Regency through training using digital marketing. This mentoring activity uses qualitative methods as an approach to cases with snack MSMEs salsabilla. Through this community service, the sales reach of salsabilla snacks is not only face-to-face but also through the digital world, so it has the potential to increase turnover. The output results of this service include sales reach and increased sales turnover.